WHY AND HOW POLITICIANS USE SOCIAL MEDIA? UNDERSTANDING SENSEMAKING AND REPRESENTATIONS OF DIGITAL PLATFORMS. THE CASE OF “FACEBOOK” AND “TWITTER” IN THE EUROPEAN PARLIAMENT - Roginsky, Sandrine (AoIR Selected Papers of Internet Research, 2015)
This presentation is intended to show (1) the richness and complexity of user practices in relation to social media (2) the contribution of an ethnographic approach to actors’ uses and practices toward a better understanding of the manner in which they understand and make sense of social media and (3) the contribution of triangulation to validate the observations. The research provides empirical insights into how politicians make sense of social media technology and the “imaginary world” (Mésangeau, Povéda, 2013) they create, emphasizing the importance of contexts and interactions. The field of the research is the European Parliament. The research includes a mix of participant observation within the European Parliament (2009-2012) and about 60 interviews with Members of the European Parliament (MEPs) and/or their staff (2010-2014). The analysis of the representations of social media by political actors does not limit itself to ethnography of situational practices and includes the analysis of published messages on social media platforms (Facebook and Twitter). Hine (2009) notes indeed that the ethnography of the internet should involve mobility between contexts of production and use as well as between online and offline. The research hopes to contribute to the knowledge of social media’s representations and imaginaries within the political realm, emphasizing why and how political actors use social media in everyday political life.